THE CORRELATION OF SELF-CONFIDENCE AND STUDENTS’ SPEAKING ACHIEVEMENT THROUGH THE MODIFIED BUDDY SYSTEM WITH COMMUNICATIVE LANGUAGE TEACHING PRINCIPLES - Ervina Agustin (Tell-us Journal)
This study investigates the correlation between self-confidence and students’ speaking achievement through the Modified Buddy System integrated with Communicative Language Teaching (CLT) principles. A quantitative research method was employed, using Pearson Product-Moment Correlation to analyze the correlation between self-confidence and speaking achievement. Speaking tests were administered to assess students' oral proficiency, while a self-confidence questionnaire measured their perceived confidence levels before and after the implementation of modified Buddy System with CLT principles. The findings indicate a significant positive correlation suggesting that students with higher self-confidence perform better in oral communication tasks. The study highlights the relevance of establishing a supportive learning environment in which students feel at ease communicating, which improves their speaking achievement and overall language competence.